Nourishing Millions: Stories of change in nutrition [All chapter presentations] - International Food Policy Research Institute (2016)
Malnutrition costs the world trillions of dollars, but global commitment to improving people’s nutrition is on the rise, and so is our knowledge of how to do so. Over the past 50 years, understanding of nutrition has evolved beyond a narrow focus on hunger and famine. We now know that good nutrition depends not only on people’s access to a wide variety of foods, but also on the care they receive and the environment they live in. A number of countries and programs have exploited this new understanding to make enormous strides in nutrition. Nourishing Millions: Stories of Change in Nutrition brings together the most intriguing stories from the past five decades to show what works in nutrition, what does not, and the factors that contribute to success. The stories gathered here examine interventions that address nutrition directly—such as community nutrition programming and feeding programs for infants and young children—as well as nutrition-sensitive policies related to agriculture, social protection, and clean water and sanitation. The authors consider efforts to combat the severest forms of acute malnutrition as well as overweight and obesity. They shed light on nutrition success stories on the ground in places ranging from Bangladesh, Brazil, Nepal, Peru, Thailand, and Vietnam to Ethiopia and the state of Odisha in India. The book also examines how nutrition “champions” emerge and drive change. Altogether, Nourishing Millions is a unique look at past and emerging nutrition successes and challenges around the world.